(untitled) (Journal of Partial Differential Equations, 2025)
In this paper, we study the following coupled nonlinear logarithmic Hartree system where β,μ_i,λ_i (i=1,2) are positive constants, ∗ denotes the convolution in R^2. By considering the constraint minimum problem on the Nehari manifold, we prove the existence of ground state solutions for β > 0 large enough. Moreover, we also show that every positive solution is radially symmetric and decays exponentially.